2022
DOI: 10.3389/fpls.2021.778663
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality in Main and Ratoon Crops of Grain Sorghum Under Different Nitrogen Rates and Planting Densities

Abstract: Ratooning is the cultivation practice of two harvests in one cropping season by producing a second crop from the original stubble, which could provide higher resource use efficiency and economic benefit compared with direct sown crops. Nitrogen (N) fertilizer and planting density (D) play a vital role in sorghum (Sorghum bicolor L.) production; however, limited information is available on the effects on yield and quality of the sorghum-ratoon system. To address this question, field experiments were conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Sorghum intercropping with some legumes has many economic returns ( 13 15 ), and the sorghum ratooning practice also has several advantages, such as no need for new seed and land preparation, covering of time of sowing, and high grain yield and quality ( 12 ). Zhou et al ( 16 ) reported that sorghum ratoon crop has high contents of starch, protein, and tannin and low fat content after application of nitrogen fertilizer. This chemical composition indicates good quality for liquor production.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum intercropping with some legumes has many economic returns ( 13 15 ), and the sorghum ratooning practice also has several advantages, such as no need for new seed and land preparation, covering of time of sowing, and high grain yield and quality ( 12 ). Zhou et al ( 16 ) reported that sorghum ratoon crop has high contents of starch, protein, and tannin and low fat content after application of nitrogen fertilizer. This chemical composition indicates good quality for liquor production.…”
Section: Introductionmentioning
confidence: 99%
“…Precision agriculture uses data and technology to enhance the efficiency of fertiliser application by optimising rates and timing, thereby minimising wastage and enhancing crop absorption. Cover crops may effectively scavenge residual nitrogen in the soil and mitigate leaching [80,83,84].…”
Section: Soilgenic Technologiesmentioning
confidence: 99%
“…At present, some studies focus on the analysis of the stress resistance mechanism of sorghum and the identi cation of seed development regulatory loci. For example, Calone et al 16 studied the mechanism of salt tolerance and Na in sorghum through experiments; Zhou et al 17 revealed the effects of different nitrogen application rates and planting densities on sorghum grain yield and quality and Ahn et al 1 identi ed some SNP loci that regulate the morphological development of sorghum seeds through genome-wide association analysis.…”
Section: Introductionmentioning
confidence: 99%